Ocurrencia de la enfermedad Hoja de malvon en zonas vitícolas de Catamarca y La Rioja, Argentina - Carrasco, Franca Denise; Oviedo, Hector Javier; Gonzalez Ribot, Joaquin Victor; Sosa, Pablo Antonio; Sosa, Flavio Isaac; Maza, Claudia Elizabeth; Bustos, E.; Longone, Maria Valeria; Escoriaza, Maria Georgina (Asociacion Argentina de Fitopatologia, 2021)
Poster